1994
DOI: 10.3354/meps114059
|View full text |Cite
|
Sign up to set email alerts
|

Piscivory and prey size selection in young-of-the-year bluefish: predator preference or size-dependent capture success?

Abstract: Young-of-the-year bluefish Pomatomus saltatrix become piscivorous at a very small size/age. When feeding on Atlantic silversides Menidia menidia in the laboratory, bluefish forage in groups and, unlike many other piscivores, tend to attack their prey tail-first. Attack distances, times and velocities as well as attack rates were not size-dependent Handling tlmes and attack success rates, howcver, were strongly determined by both predator and prey slze When given a choice of silverside sizes, all bluefish sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 63 publications
(80 reference statements)
7
114
0
3
Order By: Relevance
“…Whether this is true for M. menidia is unknown. Predation is a major source of mortality for silversides during the growing season (Juanes and Conover 1995). The main predators of silversides (P. saltatrix, M. saxatilis, and weakfish, Cynoscion regalis) are all more abundant south of Cape Cod than to the north (Bigelow and Schroeder 1953;Murdy et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this is true for M. menidia is unknown. Predation is a major source of mortality for silversides during the growing season (Juanes and Conover 1995). The main predators of silversides (P. saltatrix, M. saxatilis, and weakfish, Cynoscion regalis) are all more abundant south of Cape Cod than to the north (Bigelow and Schroeder 1953;Murdy et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Predators were captured with haul seines and transported to FPML where they were acclimatized to experimental tanks for 1-3 weeks prior to trials. Most trials involved P. saltatrix because it is the principal predator of silversides in many locations (Friedland et al 1988;Conover 1994, 1995;. All predators were maintained on a diet of live silversides drawn from NS and SC laboratory stocks, and all prey were trained to recognize predators through constant exposure during rearing.…”
Section: Experimental Subjectsmentioning
confidence: 99%
“…Three bluefish or seabass were used in each predator-prey trial because this number of individuals has been shown to allow for normal schooling and feeding behaviors of roving fishes (Juanes and Conover, 1994;Scharf et al, 1998;Staudinger and Juanes, 2010c). Although flounder are considered solitary animals, previous experiments (Staudinger andJuanes, 2010b, c, 2011) have shown that these lie-andwait predators may not move for hours and may not attack unless a prey is within a single body length.…”
Section: Predator-prey Trialsmentioning
confidence: 99%
“…Cependant, les prédateurs des jeunes poissons peuvent s'alimenter autant des plus petits individus, plus vulnérables (Juanes et Conover 1994), que des plus gros, plus visibles et offrant un meilleur gain énergétique (Pépin et Shears 1995;Gleason et Bengtson 1996).…”
Section: Mise En Garde/adviceunclassified